Editorial: accommodating multiple interests in local forest management - Wollenberg, Eva Karoline; Edmunds, D.; Anderson, J. (2001)
The authors introduce the special issue on accommodating multiple interests in forest management and provide an overview of the seven papers in the issue. The papers document and analyze existing approaches and from them identify principles related to pluralism and good governance. Three themes emerged from the papers. First, there are serious pragmatic and theoretical difficulties in defining interests and reaching agreements. The papers demonstrated the diversity of interests that exist in apparently homogeneous groups, the tendency for interests to be constructed in response to specific contexts and for strategic purposes, and the partial and temporary nature of agreements. Second, the papers suggest that accommodation is not a steady-state condition that can be achieved, but instead a process that is necessarily ongoing. Third, weaker groups’ interests were routinely ignored or negotiated away. Certain parties enjoyed disproportionate control because of a lack of democratic practice in (1) who assumed the convenor and facilitation roles (or controlled them), (2) who was represented in the process, and (3) differing capacities for communication and negotiation among participants.